A novel clear foil cushion construction incorporating an additional water layer - Xie, Fei (2011)
Pneumatic clear foil cushion systems, notably as ETFE foil cushions have been developed as an alternative technology to large-scale glass glazing systems for wide-span buildings. The systems display better thermal performance and have advantages of extremely low dead-weight constructions compared to conventional glazing systems, and thereby the increasing popularity of foil cushion cladding systems have been witnessed in the last decades. However due to their lightweight and thinness, the thermal behaviour of architectural foil membranes exhibits a high responsiveness to variations in external conditions. For this reason, it is argued that the reliable prediction of the thermal environment experienced in a space enclosed by a tensile membrane skin construction would require a bespoke modelling of the dynamic thermal behaviour of such a construction at first. Building envelopes clad with such cushions, such as the famous Eden project in the UK, need a dynamic system to control overheating in summer. A cooling liquid layer constructed within a clear multi-layer toil cushion envelope is proposed in this thesis. It enables rapid cooling effects on the building envelope. The system is based on an evaporative cooling mechanism and is integrated with the inflated cushion to provide desired cooling effect eco-friendly. The implications of the forms and configurations of clear foil cushion constructions with and without a cooling liquid layer in the overheating control were evaluated in this research project. Data were collected from a series of experiments to ascertain the effects of the additional cooling water layer on heat transfer processes within the foil skin construction. The results demonstrated that the thermal behaviour of a foil penal depended mainly on surface convection and radiation heat transfer and the cooling performance of the water layer within the foil skin constructions was evident. The initial experimental outcomes were valuable for the design of such novel dynamic cooling systems. In order to assess the effect that different pneumatic foil skin constructions with a water layer might have on thermal conditions inside the enclosed space, the thermal behaviour of full-scale indoor double-layer foil cushion enclosure and triple-layer foil skin construction, with varying evaporative cooling integrative ways and foil skin constructions, were tested during the course of this research. The test datasets were compared according to the research objectives and with the environmental control strategy proposed at the initial design stages. The investigated thermal behaviour of the foil skin constructions incorporating a water layer serves as a reference basis for the analytic modelling of the tested double and triple-layer foil skin constructions in order to predict their surface temperatures and the solar radiation directed into the space they enclose. The approach is based on a detailed modelling of the radiative and convective heat transfer processes affecting the membrane surfaces. These prediction results derived from the model were compared against the environmental data obtained on the test rigs. The developed analytical model is only tentative, as some thermal transfer processes, such as long wave radiation exchanges between the foil sheets, have not been accounted for in this model. Further work is required to develop this model in order to appreciate the thermal performance of such novel foil cushion constructions more precisely and extend their building applications.